Extraction of Flow Behavior and Hall–Petch Parameters Using a Nanoindentation Multiple Sharp Tip Approach1 . Issue 4 (29th November 2016) - Leitner, Alexander; Maier‐Kiener, Verena; Kiener, Daniel
Abstract : An appealing idea to material scientists is to characterize the mechanical behavior of materials with minimal experimental effort while guaranteeing highly reliable results. Nanoindentation is a candidate technique to reach this objective. Though it is already a standard method to extract hardness and Young's modulus, the technique is not yet fully exploited. The authors demonstrate on the example of Ni and W, with microstructures ranging from single crystalline to nanocrystalline dimensions, how Hall–Petch parameters and flow curves can be extracted by using four pyramidal tips with varying apex angle. Applying appropriate definitions of indentation stress and strain and considering the indentation size effect, the obtained values coincidence well with literature values determined by uniaxial tests. Abstract : Nanoindentation retrieves an enormous potential regarding the mechanical characterization of materials which can further be exploited when different tips with varying apex angle are used. We demonstrate that Hall–Petch parameters and flow behavior of Ni and W determined by a multiple sharp tip approach are in excellent agreement with values obtained by uniaxial testing.